Etyczne podstawy polityki zrównoważonego rozwoju - Mariusz Ciszek (Studia Ecologiae et Bioethicae)
The idea of sustainable development set up that at presently living people are responsible for condition of environment and they should leave future generation decent circumstances of life, this imperative of respecting of nature, activity for goods of future generation causes that every politicial operation in this range must be underpinned on certain deciding from range of ethic especially on one of its subdiscipline-environmental ethic. Unfortunately, this ethical discipline is not a monolith, because it is possible to find it’s other streams witch tries to answer a question: why should we protect the nature? Especially two opposition streams deserve notice anthropocentric and biocentric position, witch differently comprehend purpose and bases of protection of nature, the anthropocentrism has on respect goods of the person but biocentrism goods of whole nature, witch one of the many elements is a man. In this publication I try to establish, witch from this two ethical models is most optimal for practical, political programs of accustoming of sustainable development.